A medida da obsolescência na literatura de educação: uma contribuição ao entendimento da cronologia das citações na atividade científica - Coimbra, Lourdes Cristina Araujo (2015)
This study developed an exploratory and quantitative study, which included 21,846 citations were analyzed in 150 theses submitted to the Faculty of Education (FE), Federal University of Rio de Janeiro (UFRJ) Program Graduate Education (PPGE), Brazil in the period 1994-2011 in order to determine the life-half and obsolescence of literature; contribute to the decision-making units of information regarding the relocation of collections less used; Education analysis of the literature; identify the preferences of doctoral students in the act of citing documents regarding typology, regarding language, as to quote their mentors and how to self-citation. The total citations analyzed only 21,289 citations were used to calculate the life-half: 16 references were incomplete, mentioning only the author and title and 541 were without publication date, therefore not considered in the calculation. The result revealed that the literature of Education has life-half of 19 years, ie, a literature that is somewhat older, but does not disappear. It is used in historical research which can be confirmed with the presence of citations to older material, eg, 1 citation XVIII (1786) and 68 of the nineteenth century (1824-1898) century. As can be seen from the total of 150 theses analyzed, only 44 is available online, equivalent to 29.33% of this scientific production, a significant demand for this area of knowledge. It was evident that the number of doctoral students who cite their own publications equals the number who cite their advisors, with different amount of works cited, falling mostly in the work of counselors. One can prove through this research that the preferred channel of educators are books.